2011
DOI: 10.2135/cropsci2010.04.0187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maturity, Genotypic Background, and Temperature on Seed Mineral Composition in Near‐Isogenic Soybean Lines in the Early Soybean Production System

Abstract: The objective of this study was to investigate the effects of maturity, genotypic background, and maximum temperature 20 d before maturity on soybean [Glycine max (L.) Merr.] seed mineral concentrations. A field experiment was conducted in Stoneville, MS, in 2004 and 2005, using two sets of near-isogenic soybean lines that differed in maturity genes. One set of isolines derived from cultivar Clark and the other from cultivar Harosoy. The maturity of each line within a set varied, but all had a common genotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 57 publications
4
61
0
Order By: Relevance
“…During this experiment, the contribution of maturity genes and genotypic background were quantified, and found to reach 43% for maturity and 84% for genotypic ground (Bellaloui et al, 2011). Research available in this area indicated down-regulation occurred in the mutant cotton at fiber elongation stage, cellulose synthases and sucrose synthase secondary cell wall biosynthesis stage, and minerals, especially K, Ca, and B.…”
Section: Discussionmentioning
confidence: 99%
“…During this experiment, the contribution of maturity genes and genotypic background were quantified, and found to reach 43% for maturity and 84% for genotypic ground (Bellaloui et al, 2011). Research available in this area indicated down-regulation occurred in the mutant cotton at fiber elongation stage, cellulose synthases and sucrose synthase secondary cell wall biosynthesis stage, and minerals, especially K, Ca, and B.…”
Section: Discussionmentioning
confidence: 99%
“…Seed contains about 9–12% total soluble carbohydrates, including sucrose (4–5%), raffinose (2%), and stachyose (3.5–4.5%) (Wilson, 1995; Wilson et al, 1995). Seed macro- and micro-nutrients concentrations for soybean were previously reported (Zobiole et al, 2010; Bellaloui et al, 2011), and their ranges were depended on genotype, maturity, environmental factors including temperature, drought, and disease pressure (Bellaloui et al, 2011, 2012a,b). Because soybean seed contains phenolics, including lignin and isoflavones which are antioxidants, it was thought to have health benefits against osteoporosis, cancer, and heart disease for humans (Messina et al, 1994; Potter et al, 1998; Sakthivelu et al, 2008), and a role in plant disease resistance and defense mechanisms (Paxton, 1980; Graham, 1983; Graham and Webb, 1991; Dixon, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Soybean is a major crop in the world, and soybean seed is an important source for protein and oil (Belewu & Belewu 2007) and other nutrients including sugars and mineral nutrients (Hou et al 2009;Zobiole et al 2010;Bellaloui et al 2010Bellaloui et al , 2011. Soybean protein ranges from 341 to 568 g kg −1 of total seed weight, with a mean of 421 g kg −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Seed sugars include sucrose (4%-5%), raffinose (2%), and stachyose (3.5%-4.5%; Wilson, Novitzky, & Fenner 1995). Seed macro-and micro-nutrients concentrations for soybean were previously reported (Zobiole et al 2010;Bellaloui et al 2010Bellaloui et al , 2011.…”
Section: Introductionmentioning
confidence: 99%